Determinants of a silent (R)evolution: Understanding the expansion of family policy in rich OECD countries - Ferragina, E; Seeleib-Kaiser, M (Oxford University Press (OUP), 2014)
This paper contributes to the comparative social policy literature in two ways. First, we use multiple correspondence analysis in order to assess the different directions and the degree of (employment-oriented) family policy change over the past three decades in 18 rich Organisation for Economic Co-operation and Development (OECD) countries. Second, we perform a series of correlations to identify the core drivers of these developments. Our main findings—based on five international datasets—are: (i) we have been witnesses of a significant expansion of family policies over the past three decades in almost all countries analysed, although the degree of change (distinguished by first-, second- and third-order change) differs across the OECD area; and (ii) whilst in the 1980s and 1990s social democracy and organised women were key drivers of family policy expansion, during the 2000s public opinion, that increasingly seems to support a “modernised” family lifestyle in which mothers are employed, seems to have played an essential role in explaining policy change.